Peran Digital UMKM dalam Meningkatkan Daya Saing: Studi Kasus UMKM Halal Kota Medan - Mustika Ayu Anggreini; Zuhrinal M Nawawi (Jurnal Riset Akuntansi, 2025)
Digital transformation has become a strategic necessity for Micro, Small, and Medium Enterprises (MSMEs) in responding to global competition, including halal MSMEs in Medan City, which possess significant potential but still face challenges in accessing technology, mastering digital skills, and reaching broader markets. This study aims to analyze the role of digital marketing in enhancing the competitiveness of halal MSMEs, identify the benefits obtained from the implementation of digital strategies, and uncover the obstacles encountered during the digitalization process. Employing a qualitative approach with a case study design, primary data were collected through in-depth interviews, field observations, and documentation from seven halal MSMEs in Medan City. The findings indicate that the active utilization of digital marketing, particularly through social media and e-commerce platforms, contributes to increased business visibility, expanded consumer reach, and enhanced customer loyalty. However, the digitalization process remains hindered by low digital literacy, limited infrastructure, and a shortage of skilled labor. These findings affirm the importance of integrating halal values with digital technology as an effective adaptive strategy in addressing modern market dynamics. This research offers a conceptual contribution to the literature on the synergy between digitalization and the halal economy and provides practical implications for MSME actors and policymakers in designing contextually relevant and sustainable digital empowerment programs.